Employment effects of language training for unemployed immigrants - Julia Lang (Journal of Population Economics, 2021)
Proficiency in the host country's language is an important factor for the successful labor market integration of immigrants. In this study, I analyze the effects of a language training program for professional purposes on the employment opportunities of participants in Germany. I apply an instrumental variable approach and exploit differences in lagged local training intensities. Bivariate probit estimates show that 2 years after the program started, the employment probability of immigrants who were unemployed in 2014 and participated in the program had increased by more than nine percentage points as a result of language training.
Keywords: J24; J61; J68; 330; Language training; Migration; Integration; Employment